Konstruksi Kausatif dalam Bahasa Mandailing: Kajian Tipologi Sintaksis - Ibnu Ajan Hasibuan (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This article purposes to analyze the causative construction of Mandailing language as a typology in morphosyntaxis. This study provides an overview of the Mandailing contstruction forms that were often used by people in their daily lives as natural language in South Tapanuli District. The Methode used qualitative descriftive method. The data was obtained through proficient methods, record by analyzing in a conversation. Intuitive data were analyzed through morphemes and causative verbs of the Mandailing Batak language. The results of the analysis of the data on this study present an informal method in the form of exposure to three parts morphosyntactically causative construction including analytic, morphological, and lexical which the verb mambaen ‘make’ part of the causative verb. The Mandailing causative affixes of the Batak Mandailing to the results of the analysis are (ma-ko), (tar), (pa-kon), (pa-on), and (pa) in the causative morphology. Semantic parameters also have the same verb but have different meanings.